MODERN CLIMATE CHANGE IN MOUNTAIN COUNTRIES: (on the example of the Altai-Sayan Mountain country and the Caucasus) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The analysis of changes in the temperature regime in the Altai-Sayan Mountain country and in the Caucasus in the Republic of Armenia is presented. The values of slope coefficients of linear air temperature trends in mountain basins and wide valleys were obtained. Temperature trends at the highest mountain stations close to the free atmosphere were studied. Standard 30-year climatic periods recommended by the World Meteorological Organization were used. Features of similarities and differences in temperature trends up to 2020 were considered. It was shown that it is important to take into account anthropogenic factors, as well as circulation processes in the atmosphere for prognostic climate models.
Keywords: climate; Altai; Sayan Mountains; Caucasus; Republic of Armenia; temperature; orography; atmospheric circulation